Identifying potential causes of fish declines through local ecological knowledge of fishers in the Ganga River, eastern Bihar, India. (2nd October 2019) - Dey, Subhasis; Choudhary, Sunil Kumar; Dey, Sushant; Deshpande, Kadambari; Kelkar, Nachiket
Abstract: Local ecological knowledge (LEK) can offer insights into fisheries management by describing long‐term changes that are difficult to unravel in data‐poor river‐floodplain fisheries. LEK is derived from complex interactions between fishers' observations of environmental change and their institutional capacities to manage fisheries. Hence, it is important to understand where and how LEK and formal scientific studies on fish species' decline could complement each other. In this paper, the causes of decline of 58 fish and two shrimp taxa were identified from LEK data (1999–2019) obtained from river–floodplain fisheries of the Gangetic plains (Bihar, India). Qualitative analyses of LEK were used to generate species‐specific hypotheses and historical insights on their declines. Destructive fishing, overfishing and the Farakka barrage were cited by fishers as the major causes of declines. Potential reasons for these perceptions were explored in relation to fishers' experiences of conflicts in the region over fishing rights and access.